KESETARAAN GENDER DALAM PERSPEKTIF PENDIDIKAN ISLAM (STUDI KOMPARASI ATAS PEMIKIRAN FATIMA MERNISSI DENGAN MUHAMMAD QURAISH SHIHAB) - Aminatul Rizqa Oktifia; Chalimatus Sa’dijah; Imam Safi’i (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Gender differences will not actually be a problem if it does not give birth to a form of gender inequality. But in reality, these differences give birth to many forms of gender inequality. Education is an important component. Where in its activities is a process of internalizing knowledge and intellectual values. Fatima Mernissi is one of the Islamic feminists fighting for gender equality, and Muhammad Quraish Shihab is one of the writers on gender equality. Both are figures who both disagree with the justification of acts of gender injustice on the pretext of religion. This study is a literature review. The type of research is critical analysis using a library research approach. The method used is a documentation study, while the data analysis study uses content analysis and comparison. The results of the comparison of the thoughts of the two figures are: before God, men and women have the same position, the only difference is their piety (spiritual). As such, men and women have equal roles and opportunities to receive proper and proper education. Kata Kunci: Kesetaraan Gender, Pendidikan Islam, Fatima Mernissi, Muhammad Quraish Shihab